Studi Kinerja Jaringan LoRa: Optimalisasi dan Analisis Efisiensi Komunikasi Nirkabel - Liya Yuni Astutik (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
LoRa is a long-range wireless connectivity technology, considered an innovative solution for implementing the Internet of Things (IoT). This research encompasses a series of performance tests conducted under various conditions, including Line of Sight (open) and Non-Line of Sight (closed), utilizing the ISM 915 MHz frequency. The importance of testing optimization and efficiency analysis of LoRa is a key factor in ensuring the optimal performance and sustainability of this technology. The testing process involves several stages. The first test assesses the communication range of LoRa SX1276 within a building, determining its communication capabilities indoors. The second test focuses on the maximum communication range, identifying the farthest distance at which LoRa SX1276 can maintain a stable and reliable connection. The third test evaluates the performance of data transmission in a closed environment, specifically Non-Line of Sight conditions, to assess how well LoRa SX1276 maintains data transmission performance in situations with obstacles or hindrances. The fourth test assesses the resilience of LoRa SX1276 in long-term operations, evaluating the network's durability and reliability over an extended period. The fifth test conducts a comprehensive analysis of the system's performance, including aspects such as delay, data delivery, and data loss. This research aims to provide a deeper understanding of the capabilities of LoRa SX1276 in various usage scenarios. The results are expected to contribute to the development and implementation of LoRa SX1276 technology in diverse applications requiring wireless connectivity with extensive range and high efficiency.